High-performance bismuth-free ZnO-Cr2O3-based voltage-sensitive ceramic, defect regulation and control preparation method and application
By selecting suitable doped oxides in ZnO-Cr2O3-based pressure-sensitive ceramics, the immovable acceptor defects at the ZnO grain boundary are solved, and the problems of instability of ceramic structure and insufficient electrical performance in the prior art are realized, and the preparation and application of high-performance bismuth-free ZnO-Cr2O3-based pressure-sensitive ceramics are realized.
Patent Information
- Application Number
- CN202510111071.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The existing ZnO-Bi2O3-based pressure-sensitive ceramics are prone to volatilization during the sintering process, and there are many types of doped oxides, resulting in poor structural uniformity and sample preparation repeatability; at the same time, the grain boundary adsorption oxygen fluidity of ZnO-Cr2O3-based pressure-sensitive ceramics have strong grain boundary oxygen fluidity, resulting in unstable grain boundary double Schottky barrier structure.
By selecting suitable doped oxides, a bismuth-free ZnO-Cr2O3-based pressure-sensitive ceramic is prepared, and the solid phase sintering method is used to dopate oxides composed of divalent and trivalent small radius ions and oxides composed of trivalent or tetravalent large radius ions, forming an immovable acceptor defect at the ZnO grain boundary to stabilize the double Schottky barrier structure.
It realizes high-performance bismuth-free ZnO-Cr2O3-based voltage-sensitive ceramics with high nonlinear coefficients and high breakdown field strength and low leakage current density, which improves the electrical performance stability of the ceramics and is suitable for miniaturized electronic circuit systems.
Smart Images

Figure CN119912254A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of varistor materials, and specifically relates to a high-performance bismuth-free ZnO-Cr2O3-based varistor ceramic and a defect-controlling preparation method and application. Background Art
[0002] ZnO varistors are widely used in the field of power electronics as protection circuits due to their excellent nonlinear volt-ampere characteristics and surge absorption capabilities. The main parameters of their electrical performance are nonlinear coefficient, breakdown field strength and leakage current density. The higher the nonlinear coefficient, the shorter the varistor's response time to electronic component protection and the more accurate the overvoltage clamping. The smaller the leakage current density, the smaller the Joule heat loss flowing through the varistor when the circuit is working normally. Varistors with different breakdown field strengths can be used for overvoltage protection of different power electronic components; and with the development of device miniaturization, it is also urgent to prepare varistors with high breakdown field strength and excellent comprehensive electrical properties. Therefore, the preparation of ZnO varistors with high nonlinear coefficients and breakdown field strengths and low leakage current density is an important goal pursued by researchers. ZnO varistors are encapsulated by ZnO varistor ceramics, and their electrical properties mainly depend on the properties of ZnO varistor ceramics. ZnO varistor ceramics are made of ZnO as the main raw material, and are doped with other oxides to give them excellent electrical properties.
[0003] At present, ZnO-Bi2O3-based varistor ceramics are the most widely used. They are made of ZnO as the main raw material, doped with a small amount of Bi2O3, and doped with a small amount of other oxides, and fired by solid phase sintering. During the sintering process, Bi2O3 forms a liquid phase, dissolves a variety of oxides at the same time, and fully infiltrates around the ZnO grains. During the cooling process, a grid-like bismuth-rich phase rich in acceptor defect free oxygen is formed, distributed at the ZnO grain boundaries. At the same time, the doped oxides are solid-dissolved into the ZnO grains to form a large number of donor defects, that is, to form N-type ZnO grains. Therefore, the N-type ZnO grains and the bismuth-rich phase at the grain boundaries together form a double Schottky barrier at the grain boundaries. The double Schottky barrier at the grain boundaries is the main structural basis for determining the electrical properties of ZnO varistor ceramics. Doping or improving the sintering process is the main means to improve the characteristics of the double Schottky barrier at the grain boundaries, thereby improving the electrical properties of ZnO varistor ceramics. The current mainstream view is that doping can control the growth of ZnO grains and improve the uniformity of the microstructure; at the same time, the concentration of donors in ZnO grains and the concentration of free oxygen as acceptors at the grain boundaries can be adjusted; and the double Schottky barrier characteristics and electrical properties of the grain boundaries can be adjusted. Based on this view, researchers have done a lot of work to improve the electrical properties of ZnO-Bi2O3-based varistors, and obtained varistors with excellent electrical properties. However, since Bi2O3 is easily volatilized during the sintering process of ZnO-Bi2O3-based varistors and there are many types of doped oxides, their structural uniformity and sample preparation repeatability are poor, which seriously restricts their application. In recent years, researchers have developed bismuth-free ZnO-Cr2O3-based varistors, which have the advantages of no volatilization of doped oxides during sintering, fewer types of doped oxides, and simple structure. People have studied the effect of doping on the microstructure and electrical properties of ZnO-Cr2O3-based varistor ceramics. At the same time, referring to the research on ZnO-Bi2O3-based varistor ceramics, it is pointed out that doping can increase the concentration of donors in ZnO grains and the concentration of adsorbed oxygen as acceptor defects in ZnO grain boundaries, thereby increasing the height of the double Schottky barrier and improving nonlinear electrical properties. However, the adsorbed oxygen at the grain boundary has good fluidity, which will inevitably lead to the instability of the double Schottky barrier structure at the grain boundary and the poor stability of the electrical properties of the varistor ceramics.
[0004] In view of the problems existing in ZnO-Bi2O3-based varistors and bismuth-free ZnO-Cr2O3-based varistors, it is urgently necessary to develop a preparation method for bismuth-free ZnO-Cr2O3-based varistors, so that immovable acceptor defects are formed at the ZnO grain boundaries, the double Schottky barrier characteristics of the grain boundaries are regulated, and then bismuth-free ZnO-Cr2O3-based varistors with high nonlinear coefficient and breakdown field strength and small leakage current density are prepared, so that they can be used in miniaturized electronic circuits. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a high-performance bismuth-free ZnO-Cr2O3-based varistor ceramic and a defect-controlled preparation method and application, so as to solve the technical problems that Bi2O3 is easily volatile during the sintering process of the existing ZnO-Bi2O3-based varistor ceramics, and there are many types of doped oxides, resulting in poor structural uniformity and sample preparation repeatability, and the ZnO-Cr2O3-based varistor ceramics have strong adsorbed oxygen mobility at the grain boundaries, resulting in unstable double Schottky barrier structure at the grain boundaries.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention discloses a method for preparing high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics by regulating defects, comprising the following steps: The ZnO, doped oxide, polyvinyl alcohol aqueous solution, tributyl phosphate and deionized water are ball-milled and mixed to obtain a mixed powder; after drying, sieving granulation and pressing, the oxide-doped ZnO green body is obtained; after debinding and sintering, a high-performance bismuth-free ZnO-Cr2O3-based varistor ceramic is obtained; Doped oxides include several oxides composed of divalent and trivalent ions of small radius, and one oxide composed of trivalent or tetravalent ions of large radius; The divalent and trivalent small radius ion oxides are Cr2O3, Co3O4 and CaCO3; The trivalent or tetravalent large-radius ion oxide is any one of Eu2O3, Dy2O3 and CeO2.
[0007] Preferably, the molar percentage of ZnO to the doping oxide is (95.00-98.00): (2.00-5.00); The mass of the polyvinyl alcohol aqueous solution is 10%-20% of the total mass of ZnO and doped oxide; The mass of tributyl phosphate is 1%-3% of the total mass of ZnO and doped oxides; The mass of deionized water is 150%-200% of the total mass of ZnO and doped oxides.
[0008] Preferably, the mass percentage of the polyvinyl alcohol aqueous solution is 3%-6%; The doping oxides do not include oxides that are volatile during the sintering process.
[0009] Preferably, the ball milling time is 6-8 hours; the sieving granulation conditions are: selecting uniform powder of 40 mesh to 120 mesh.
[0010] Preferably, the pressing conditions are as follows: every 0.15-0.25 g of the mixed powder is pressed into an oxide-doped ZnO green body with a diameter of 8.0 mm and a thickness of 0.75-1.25 mm.
[0011] Preferably, the debinding temperature is 600°C and the debinding time is 2-5 h.
[0012] Preferably, the sintering temperature is 1100° C. and the sintering time is 1-3 h.
[0013] The present invention also discloses a high-performance bismuth-free ZnO-Cr2O3-based varistor ceramic, which is prepared by the above-mentioned method for preparing a high-performance bismuth-free ZnO-Cr2O3-based varistor ceramic by regulating defects. In the high-performance bismuth-free ZnO-Cr2O3-based varistor ceramic, Cr is enriched in solid solution at the ZnO grain boundary. 3+ 、Co 3+ and Ca 2+ The oxide includes Eu2O3, Dy2O3 or CeO2; and forms an immobile acceptor defect Ca in Eu2O3, Dy2O3 or CeO2 enriched at the ZnO grain boundary. × Eu , Ca × Dy or Cr × Ce .
[0014] Preferably, the nonlinear coefficient of the high-performance bismuth-free ZnO-Cr2O3-based varistor ceramic is 66-97, the breakdown field strength is 1441-1830 V / mm, and the leakage current density is 0.12-0.76 μA / cm 2 .
[0015] The present invention also discloses the application of high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics prepared by the method for preparing high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics by regulating defects in power electronic systems.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a method for preparing high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics by regulating defects. The method adopts a solid-phase sintering method, uses ZnO as the main raw material, and dopes a variety of oxides to obtain a green body by pressing, and then sintering to obtain a bismuth-free ZnO-Cr2O3-based varistor ceramic. The core of the sample preparation in the present invention lies in the selection of doped oxides. The doped oxides do not contain oxides such as Bi2O3 that are easily volatile during the sintering process, and the types of doped oxides are relatively small, thereby avoiding the problem that Bi2O3 is easily volatile during the sintering process of the existing ZnO-Bi2O3-based varistor ceramics, and avoiding the problem that there are many types of doped oxides, resulting in poor structural uniformity and sample preparation repeatability. In the present invention, several oxides composed of divalent and trivalent ions with smaller radii (such as Cr2O3, Co3O4 and CaCO3) are doped, and an oxide composed of trivalent or tetravalent ions with larger radii (such as Eu2O3, Dy2O3 or CeO2) is doped, so that the ZnO grain boundaries are enriched with solid solution such as Cr 3+ 、Co 3+ and Ca 2+ The oxides Eu2O3, Dy2O3 or CeO2, etc., and Ca2+ is formed in the oxides Eu2O3, Dy2O3 or CeO2 enriched in the ZnO grain boundaries. × Eu , Ca × Dy Cr × Ce The immovable acceptor defects such as those in ZnO-Bi2O3-based or ZnO-Cr2O3-based varistors reported in the literature are avoided, and the problem of strong mobility of oxygen adsorbed at the grain boundaries as acceptor defects leads to unstable double Schottky barrier structure at the grain boundaries. This also provides a very important technical idea for optimizing the electrical properties of varistors of different systems.
[0017] Compared with the ZnO-Cr2O3-based varistor ceramics reported in the literature, the bismuth-free ZnO-Cr2O3-based varistor ceramics prepared by the present invention have better comprehensive electrical properties. Its nonlinear coefficient is 66-97, the breakdown field strength is 1441-1830 V / mm, and the leakage current density is 0.12-0.76 μA / cm 2 , which has broad application prospects in miniaturized electronic circuit systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is the XRD spectrum of the Eu2O3 doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Eu) prepared in Example 1 of the present invention; Figure 2It is a SEM photo of the Eu2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Eu) prepared in Example 1 of the present invention and the EDS element distribution images of the corresponding Cr, Co, Ca, and Eu elements; wherein a is a SEM photo, and b~e are EDS element distribution images of Cr, Co, Ca, and Eu elements, respectively; Figure 3 is the XRD spectrum of the Dy2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Dy) prepared in Example 2 of the present invention; Figure 4 It is a SEM photo of the Dy2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Dy) prepared in Example 2 of the present invention and the EDS element distribution images of the corresponding Cr, Co, Ca, and Dy elements; wherein a is a SEM photo, and b~e are the EDS element distribution images of the Cr, Co, Ca, and Dy elements, respectively; Figure 5 It is a SEM photo of the Dy2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Dy) prepared in Example 2 of the present invention and the EDS line scanning spectrum of the corresponding Zn, Cr, Co, Ca, and Dy elements; Figure 6 is the XRD spectrum of the CeO2-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Ce) prepared in Example 3 of the present invention; Figure 7 It is a SEM photo of the CeO2-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Eu) prepared in Example 3 of the present invention and the EDS element distribution images of the corresponding Cr, Co, Ca, and Ce elements; wherein a is a SEM photo, and b~e are EDS element distribution images of Cr, Co, Ca, and Ce elements, respectively; Figure 8 is the XRD spectrum of the Er2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Er) prepared in Comparative Example 1; Fig. 9 The SEM photo of the Er2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Er) prepared in Example 1 and the EDS element distribution images of the corresponding Cr, Co, Ca, and Er elements; wherein a is the SEM photo, and b~e are the EDS element distribution images of the Cr, Co, Ca, and Er elements, respectively; Fig.10 is the XRD spectrum of the Tm2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Tm) prepared in Comparative Example 2; Fig.11 These are the SEM photograph of the Tm2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Tm) prepared in Example 2 and the EDS element distribution images of the corresponding Cr, Co, Ca, and Tm elements; wherein a is the SEM photograph, and b~e are the EDS element distribution images of the Cr, Co, Ca, and Tm elements, respectively. DETAILED DESCRIPTION
[0019] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0021] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0022] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0023] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0024] In the present invention, unless otherwise specified, the numerical range "a~b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6~22" means that all real numbers between "6~22" have been listed in this document, and "6~22" is just an abbreviation of these numerical combinations.
[0025] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0026] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0027] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0028] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0029] The present invention provides a method for preparing high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics by regulating defects, which provides a very important technical idea for optimizing the electrical properties of varistors of different systems, and ultimately obtains high-performance bismuth-free ZnO-Cr2O3-based varistors with high nonlinear coefficient and breakdown field strength and low leakage current density, which has broad application prospects in miniaturized electronic circuit systems.
[0030] A method for preparing high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics by regulating defects comprises the following steps: 1) ZnO, doped oxide, polyvinyl alcohol aqueous solution, tributyl phosphate and deionized water are ball-milled and mixed, and then dried, sieved and granulated and pressed to obtain an oxide-doped ZnO green body; 2) The oxide-doped ZnO green body obtained in step 1) is calcined to remove binder, and further sintered to obtain bismuth-free ZnO-Cr2O3-based varistor ceramics.
[0031] In step 1), the molar percentage of ZnO and doping oxide is (95.00-98.00): (2.00-5.00); The amount of polyvinyl alcohol aqueous solution added is 10%-20% of the total mass of ZnO and doped oxide; The amount of tributyl phosphate added is 1%-3% of the total mass of ZnO and doped oxide; The amount of deionized water added is 150%-200% of the total mass of ZnO and doped oxide; The mass percentage of polyvinyl alcohol aqueous solution is 3%-6%; Doped oxides include several oxides composed of divalent and trivalent ions with smaller radius (such as Cr2O3, Co3O4 and CaCO3), and one oxide composed of trivalent or tetravalent ions with larger radius (such as Eu2O3, Dy2O3 or CeO2), and do not include oxides such as Bi2O3 that are volatile during sintering; The ball milling time is 6-8h; The sieving and granulating conditions are: selecting uniform powder from 40 mesh to 120 mesh.
[0032] When the powder is pressed into shape, 0.15-0.25 g of the powder is taken and pressed into a green body with a diameter of 8.0 mm and a thickness of 0.75-1.25 mm.
[0033] In step 2), the debinding temperature is 600 °C and the debinding time is 2-5 h; The sintering temperature is 1100 °C and the sintering time is 1-3 h.
[0034] The present invention also discloses a bismuth-free ZnO-Cr2O3-based varistor ceramic prepared by the above-mentioned preparation method, wherein the ZnO grain boundaries are enriched with solid solution such as Cr 3+ 、Co 3+ and Ca 2+ The oxides Eu2O3, Dy2O3 or CeO2, etc., and Ca2+ is formed in the oxides Eu2O3, Dy2O3 or CeO2 enriched in the ZnO grain boundaries. × Eu , Ca × Dy Cr × Ce etc. immovable acceptor defects.
[0035] The present invention also discloses a bismuth-free ZnO-Cr2O3-based varistor ceramic prepared by the above preparation method, which has a nonlinear coefficient of 66-97, a breakdown field strength of 1441-1830 V / mm, and a leakage current density of 0.12-0.76 μA / cm 2 .
[0036] The invention also discloses the application of the bismuth-free ZnO-Cr2O3-based varistor ceramics prepared by the preparation method in a power electronic system.
[0037] The present invention discloses a high-performance bismuth-free ZnO-Cr2O3-based varistor ceramic and a defect-control preparation method and application, which solve the problems of the existing ZnO-Bi2O3-based varistor ceramics that Bi2O3 is easily volatile during the sintering process and that there are many types of doped oxides, resulting in poor structural uniformity and sample preparation repeatability, and the problem that the ZnO-Cr2O3-based varistor ceramics have strong oxygen adsorption mobility at the grain boundaries, resulting in unstable double Schottky barrier structures at the grain boundaries. It also provides a very important technical idea for optimizing the electrical properties of varistors of different systems; and prepares high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics with high nonlinear coefficients and breakdown field strength and low leakage current density that can be used in miniaturized electronic circuits.
[0038] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] Example 1 The preparation method of Eu2O3 doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramics comprises the following steps: 1) According to the best performance formula 96.65 mol% ZnO + 0.10 mol% Cr2O3 + 0.50 mol% Co3O4 + 2.00 mol% CaCO3 + 0.75 mol% Eu2O3, 10 g of oxide powder was weighed and placed in a nylon ball mill together with 18 g of deionized water, 2 g of 4% polyvinyl alcohol (PVA) aqueous solution, and 0.1 g of tributyl phosphate. The mixture was ball milled at 500 r / min for 7 h using a planetary ball mill. The obtained slurry was dried at 90 °C for 12 h to obtain a mixed powder. 2) Grind and sieve the mixed powder obtained in step 1), select uniform powder between 40 mesh and 120 mesh, weigh 0.15 g of the powder, and uniaxially press to obtain a green body with a diameter of 8.0 mm and a thickness of 0.75 mm; 3) The green body prepared in step 2) was heated to 600 °C at a rate of 3 °C / min and kept for 5 h for debinding, then heated to 1100 °C at a rate of 3 °C / min and kept for 3 h, then cooled to 500 °C at a rate of 3 °C / min, and then naturally cooled to room temperature to obtain Eu2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramics, with the sample number being Zn-Eu.
[0040] See also Figure 1 This is the XRD spectrum of the Eu2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Eu) prepared in Example 1 of the present invention; it can be seen from the spectrum that, in addition to the ZnO phase, the sample mainly contains the Eu2O3 phase.
[0041] See also Figure 2The SEM photo of the Eu2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Eu) prepared in Example 1 of the present invention and the EDS element distribution images of the corresponding Cr, Co, Ca, and Eu elements; where a is the SEM photo, and b~e are the EDS element distribution images of Cr, Co, Ca, and Eu elements, respectively; it can be seen from the figure that the enrichment overlap of Eu and Ca is the highest, and a small amount of Cr, Co, and Eu distribution overlap. Figure 1 It can be seen that part of Ca is dissolved in the Eu2O3 phase, and a small amount of Cr and Co are also dissolved in the Eu2O3 phase and distributed at the ZnO grain boundary. Ca is dissolved in the Eu2O3 phase to form an immovable acceptor defect Ca × Eu , leading to the formation of a stable double Schottky barrier structure at the ZnO grain boundary, further improving the electrical properties of the sample.
[0042] Example 2 The preparation method of Dy2O3 doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramics comprises the following steps: 1) According to the best performance formula 96.40 mol% ZnO + 0.10 mol% Cr2O3 + 0.50 mol% Co3O4 + 2.00 mol% CaCO3 + 1.00 mol% Dy2O3, 10 g of oxide powder was weighed and placed in a nylon ball mill together with 18 g of deionized water, 2 g of 4% polyvinyl alcohol (PVA) aqueous solution, and 0.1 g of tributyl phosphate. The mixture was ball milled at 500 r / min for 8 h using a planetary ball mill. The obtained slurry was dried at 90 °C for 12 h to obtain a mixed powder. 2) Grind and sieve the mixed powder obtained in step 1), select uniform powder between 40 mesh and 120 mesh, weigh 0.15 g of the powder, and uniaxially press to obtain a green body with a diameter of 8.0 mm and a thickness of 0.75 mm; 3) The green body prepared in step 2) was heated to 600 °C at a rate of 3 °C / min and kept for 5 h for debinding, then heated to 1100 °C at a rate of 3 °C / min and kept for 3 h, then cooled to 500 °C at a rate of 3 °C / min, and then naturally cooled to room temperature to obtain Dy2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramics, with the sample number being Zn-Dy.
[0043] See also Figure 3This is the XRD spectrum of the Dy2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Dy) prepared in Example 2 of the present invention; it can be seen from the spectrum that, in addition to the ZnO phase, the sample mainly contains the Dy2O3 phase.
[0044] See also Figure 4 The SEM photograph of the Dy2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Dy) prepared in Example 2 of the present invention and the EDS element distribution images of the corresponding Cr, Co, Ca, and Dy elements; wherein, a is the SEM photograph, and b~e are the EDS element distribution images of the Cr, Co, Ca and Dy elements, respectively; it can be seen from the figure that there is overlap in the enrichment of Dy and Ca, and Cr and Co are distributed more evenly in the whole sample.
[0045] because Figure 4 The overlap between Dy and Ca distributions is not intuitive enough, see Figure 5 The SEM photo of the Dy2O3 doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Dy) prepared in Example 2 of the present invention and the EDS line scanning spectrum of the corresponding Zn, Cr, Co, Ca, and Dy elements are given; it can be seen from the figure that the enrichment of Dy and Ca overlaps, and the distribution of Cr and Co is relatively uniform. Figure 3 and 4 It can be seen that part of Ca is dissolved in the Dy2O3 phase and distributed at the ZnO grain boundary. Dy is dissolved in the Eu2O3 phase to form an immovable acceptor defect Ca × Dy , leading to the formation of a stable double Schottky barrier structure at the ZnO grain boundary, further improving the electrical properties of the sample.
[0046] Example 3 The preparation method of CeO2 doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramics comprises the following steps: 1) According to the best performance formula 96.40 mol% ZnO + 0.10 mol% Cr2O3 + 0.50 mol% Co3O4 + 2.00 mol% CaCO3 + 1.00 mol% CeO2, 10 g of oxide powder was weighed and placed in a nylon ball mill together with 18 g of deionized water, 2 g of 4% polyvinyl alcohol (PVA) aqueous solution, and 0.1 g of tributyl phosphate. The mixture was ball milled at 500 r / min for 6 h using a planetary ball mill. The obtained slurry was dried at 90 °C for 12 h to obtain a mixed powder. 2) Grind and sieve the mixed powder obtained in step 1), select uniform powder between 40 mesh and 120 mesh, weigh 0.15 g of the powder, and uniaxially press to obtain a green body with a diameter of 8.0 mm and a thickness of 0.75 mm; 3) The green body prepared in step 2) was heated to 600 °C at a rate of 3 °C / min and kept for 5 h for debinding, then heated to 1100 °C at a rate of 3 °C / min and kept for 3 h, then cooled to 500 °C at a rate of 3 °C / min, and then naturally cooled to room temperature to obtain CeO2-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramics, with the sample number being Zn-Ce.
[0047] See also Figure 6 This is the XRD spectrum of the CeO2-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Ce) prepared in Example 3 of the present invention; it can be seen from the spectrum that, in addition to the ZnO phase, the sample mainly contains the CeO2 phase.
[0048] See also Figure 7 The SEM photo of the CeO2-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Eu) prepared in Example 3 of the present invention and the EDS element distribution images of the corresponding Cr, Co, Ca, and Ce elements; where a is the SEM photo, and b~e are the EDS element distribution images of Cr, Co, Ca, and Ce elements, respectively; it can be seen from the figure that the enrichment overlap of Ce and Cr is relatively high. Figure 6 It can be seen that part of Cr is dissolved in the CeO2 phase and distributed at the ZnO grain boundary. Cr is dissolved in the CeO2 phase to form an immovable acceptor defect Cr × Ce , leading to the formation of a stable double Schottky barrier structure at the ZnO grain boundary, further improving the electrical properties of the sample.
[0049] Example 4 The preparation method of Eu2O3 doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramics comprises the following steps: 1) According to the best performance formula 95.00 mol% ZnO +0.25 mol% Cr2O3+ 1.00 mol% Co3O4+2.50 mol% CaCO3+1.25 mol% Eu2O3, 10 g of oxide powder was weighed and placed in a nylon ball mill together with 20 g of deionized water, 1 g of 6% polyvinyl alcohol (PVA) aqueous solution, and 0.3 g of tributyl phosphate. The mixture was ball milled at 500 r / min for 6 h using a planetary ball mill. The obtained slurry was dried at 90 °C for 12 h to obtain a mixed powder. 2) Grind and sieve the mixed powder obtained in step 1), select uniform powder between 40 mesh and 120 mesh, weigh 0.25 g of the powder, and uniaxially press to obtain a green body with a diameter of 8.0 mm and a thickness of 1.25 mm; 3) The green body prepared in step 2) was heated to 600 °C at a rate of 3 °C / min and kept for 2 h for debinding, then heated to 1100 °C at a rate of 3 °C / min and kept for 1 h, then cooled to 500 °C at a rate of 3 °C / min, and then naturally cooled to room temperature to obtain Eu2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramics, sample numbered Zn-Eu-1.
[0050] Example 5 The preparation method of CeO2 doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramics comprises the following steps: 1) According to the best performance formula 98.00 mol% ZnO + 0.10 mol% Cr2O3 + 0.15 mol% Co3O4 + 1.00 mol% CaCO3 + 0.75 mol% CeO2, 10 g of oxide powder was weighed and placed in a nylon ball mill together with 15 g of deionized water, 2 g of 3% polyvinyl alcohol (PVA) aqueous solution, and 0.2 g of tributyl phosphate. The mixture was ball milled at 500 r / min for 6 h using a planetary ball mill. The obtained slurry was dried at 90 °C for 12 h to obtain a mixed powder. 2) Grind and sieve the mixed powder obtained in step 1), select uniform powder between 40 mesh and 120 mesh, weigh 0.2 g of the powder, and uniaxially press to obtain a green body with a diameter of 8.0 mm and a thickness of 1 mm; 3) The green body prepared in step 2) was heated to 600 °C at a rate of 3 °C / min and kept for 3 h for debinding, then heated to 1100 °C at a rate of 3 °C / min and kept for 2 h, then cooled to 500 °C at a rate of 3 °C / min, and then naturally cooled to room temperature to obtain CeO2-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramics, sample numbered Zn-Ce-1.
[0051] Finally, the oxide-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramics prepared in Examples 1-5 are polished, silver-coated, dried, and then silver electrodes are sintered to reduce the silver oxide to elemental silver and fit tightly to the sample surface as an electrode to facilitate testing of its electrical properties.
[0052] See Table 1 for the electrical properties of high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics prepared in Examples 1-5. It can be seen from the table that the nonlinear coefficient of the sample prepared in Example 1 is α 79, breakdown field strength E 1 mA 1830 V / mm, leakage current density J L 0.76 μA / cm 2 ; Non-linear coefficient of the sample obtained in Example 2 α 66, breakdown field strength E 1 mA 1507 V / mm, leakage current density J L 0.16 μA / cm 2 ; Non-linear coefficient of the sample obtained in Example 3 α 97, breakdown field strength E 1 mA 1441 V / mm, leakage current density J L 0.12 μA / cm 2 ; Non-linear coefficient of the sample obtained in Example 4 α 67, breakdown field strength E 1 mA 1688V / mm, leakage current density J L 0.65 μA / cm 2 ; Non-linear coefficient of the sample obtained in Example 5 α 73, breakdown field strength E 1 mA 1523 V / mm, leakage current density J L 0.45 μA / cm 2 In summary, the bismuth-free ZnO-Cr2O3-based varistor ceramics prepared in Examples 1-5 have a high nonlinear coefficient (66-97), a high breakdown field strength (1441-1830 V / mm), and a low leakage current density (0.12-0.76 μA / cm 2 ) and other excellent electrical properties, and has broad application prospects in miniaturized electronic circuit systems. Figure 1-7 It can be seen that for the above-obtained bismuth-free ZnO-Cr2O3-based varistor ceramics, Ca is formed in the oxides such as Eu2O3, Dy2O3 or CeO2 enriched in the ZnO grain boundaries. × Eu , Ca × Dy Cr × CeThe immovable acceptor defects such as ZnO lead to the formation of a stable double Schottky barrier structure at the ZnO grain boundary, which further leads to the excellent electrical properties of the sample.
[0053] Table 1 Electrical properties of high performance bismuth-free ZnO-Cr2O3 based varistor ceramics prepared in Examples 1-3
[0054] Comparative Example 1 The preparation method of Er2O3 doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramics is different from that in Example 1, in step 1), the best performance formula is 96.65 mol% ZnO + 0.10 mol%Cr2O3+ 0.50 mol% Co3O4+ 2.00 mol%CaCO3+0.75 mol% Er2O3; in step 3), Er2O3 doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramics are obtained, and the sample number is Zn-Er.
[0055] See also Figure 8 This is the XRD spectrum of the Er2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Er) prepared in Comparative Example 1; it can be seen from the spectrum that, in addition to the ZnO phase, the sample mainly contains the Er2O3 phase.
[0056] See also Fig. 9 The SEM photo of the Er2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Er) prepared in comparative example 1 and the EDS element distribution images of the corresponding Cr, Co, Ca, and Er elements; among them, a is the SEM photo, and b~e are the EDS element distribution images of Cr, Co, Ca, and Er elements respectively; it can be seen from the figure that the enrichment overlap of Er and Co is relatively high. Figure 8 It can be seen that part of Co is dissolved in Eu2O3 phase and distributed at the ZnO grain boundary. × Eu It is neither a donor nor an acceptor, and cannot improve the double Schottky barrier characteristics at the ZnO grain boundary. The improvement of the double Schottky barrier characteristics at the ZnO grain boundary in the sample is mainly attributed to the increase in the adsorbed oxygen content at the grain boundary, which has limited improvement on the electrical properties.
[0057] Comparative Example 2 The preparation method of Tm2O3 doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramics is different from that in Example 1, in step 1), the best performance formula is 96.90 mol% ZnO + 0.10 mol%Cr2O3+ 0.50 mol% Co3O4+ 2.00 mol%CaCO3+0.50 mol% Tm2O3; in step 3), Tm2O3 doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramics are obtained, and the sample number is Zn-Tm.
[0058] See also Fig.10 This is the XRD spectrum of the Tm2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Tm) prepared in Comparative Example 2; it can be seen from the spectrum that, in addition to the ZnO phase, the sample mainly contains the Tm2O3 phase.
[0059] See also Fig.11 The SEM photo of the Tm2O3-doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample (sample number: Zn-Tm) prepared in Comparative Example 2 and the EDS element distribution images of the corresponding Cr, Co, Ca, and Tm elements; where a is the SEM photo, and b~e are the EDS element distribution images of Cr, Co, Ca, and Tm elements, respectively; it can be seen from the figure that there is a certain overlap in the enrichment of Tm, Co, and Cr. Fig.10 It can be seen that part of Co and Cr are dissolved in the Tm2O3 phase and distributed at the ZnO grain boundary. × Tm Cr × Tm It is neither a donor nor an acceptor, and cannot improve the double Schottky barrier characteristics at the ZnO grain boundary. The improvement of the double Schottky barrier characteristics at the ZnO grain boundary in the sample is mainly attributed to the increase in the adsorbed oxygen content at the grain boundary, which has limited improvement on the electrical properties.
[0060] The varistor ceramic samples obtained in Comparative Example 1 and Comparative Example 2 (sample numbers are Zn-Er and Zn-Tm) are polished, silver-coated, dried, and then silver electrodes are infiltrated to reduce the silver oxide to elemental silver and closely adhere to the sample surface as an electrode to facilitate testing of its electrical properties.
[0061] See Table 2 for the electrical properties of the varistor ceramic samples obtained under the best performance formula in Comparative Example 1 and Comparative Example 2. It can be seen from the table that the nonlinear coefficient of the sample obtained in Comparative Example 1 is α 50, breakdown field strength E 1 mA 1617 V / mm, leakage current densityJ L 0.79 μA / cm 2 ; The nonlinear coefficient of the sample obtained in Comparative Example 2 α 54, breakdown field strength E 1 mA 1778 V / mm, leakage current density J L 0.97 μA / cm 2 Compared with the electrical properties of the bismuth-free ZnO-Cr2O3-based varistors obtained in Examples 1-5, the varistors obtained in Comparative Examples 1 and 2 have lower nonlinear coefficients, higher leakage current densities, and poorer overall electrical properties. Figure 8-11 It can be seen that for the bismuth-free ZnO-Cr2O3-based varistor ceramics obtained in Comparative Examples 1 and 2, the defects Co formed at the ZnO grain boundaries × Eu / Co × Tm / Cr × Tm It is neither a donor nor an acceptor, and cannot improve the double Schottky barrier characteristics at the ZnO grain boundary. The improvement of the double Schottky barrier characteristics at the ZnO grain boundary in the sample is mainly attributed to the increase in the adsorbed oxygen content at the grain boundary, which has limited improvement on electrical properties. At the same time, the adsorbed oxygen at the grain boundary has strong mobility, which leads to the problem of unstable double Schottky barrier structure at the grain boundary.
[0062] Table 2 Electrical properties of the varistor ceramic samples obtained under the best performance formula in Comparative Example 1 and Comparative Example 2
[0063] In the present invention, by selecting a suitable doping oxide, an immovable acceptor defect Ca is formed at the ZnO grain boundary in the obtained Eu2O3 / Dy2O3 / CeO2 doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample. × Eu / Ca × Dy / Cr × Ce , resulting in the formation of a stable double Schottky barrier structure at the ZnO grain boundary, further improving the electrical properties of the sample, and obtaining a higher nonlinear coefficient (66-97), a higher breakdown field strength (1441-1830 V / mm), and a smaller leakage current density (0.12-0.76 μA / cm 2) varistor ceramic samples have broad application prospects in miniaturized electronic circuit systems. In Comparative Examples 1 and 2, the Er2O3 / Tm2O3 doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic samples obtained have a defective Co × Eu / Co × Tm / Cr × Tm It is neither a donor nor an acceptor, and cannot improve the double Schottky barrier characteristics at the ZnO grain boundary; and the improvement of the double Schottky barrier characteristics at the ZnO grain boundary in the sample is mainly attributed to the increase in the adsorbed oxygen content at the grain boundary, which has limited improvement on the electrical properties. At the same time, the adsorbed oxygen at the grain boundary has strong mobility, which leads to the problem of unstable double Schottky barrier structure at the grain boundary. Compared with the present invention, the Er2O3 / Tm2O3 doped ZnO-Cr2O3-Co3O4-CaCO3 varistor ceramic sample has a lower nonlinear coefficient (50-54) and a larger leakage current density (0.79-0.97 μA / cm 2 ), the comprehensive electrical performance is poor. By comparing the embodiment of the present invention with comparative examples 1 and 2, it is found that the correct selection of doped oxide is crucial and is also the technical core of the present invention, which also provides a very important technical idea for optimizing the electrical performance of varistor ceramics of different systems.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics by controlling defects, characterized in that: The following steps are involved: The ZnO, doped oxide, polyvinyl alcohol aqueous solution, tributyl phosphate and deionized water are ball-milled and mixed to obtain a mixed powder; after drying, sieving granulation and pressing, the oxide-doped ZnO green body is obtained; after debinding and sintering, a high-performance bismuth-free ZnO-Cr2O3-based varistor ceramic is obtained; The doped oxides include several oxides composed of divalent and trivalent ions with small radius, and one oxide composed of trivalent or tetravalent ions with large radius; The divalent and trivalent small radius ion oxides are Cr2O3, Co3O4 and CaCO3; The trivalent or tetravalent large-radius ion oxide is any one of Eu2O3, Dy2O3 and CeO2.
2. The method for preparing high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics by controlling defects according to claim 1, characterized in that: The molar percentage of ZnO and doped oxide is (95.00-98.00): (2.00-5.00); The mass of the polyvinyl alcohol aqueous solution is 10%-20% of the total mass of ZnO and the doped oxide; The mass of the tributyl phosphate is 1%-3% of the total mass of ZnO and the doped oxide; The mass of the deionized water is 150%-200% of the total mass of ZnO and the doped oxide.
3. The method for preparing high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics by controlling defects according to claim 1, characterized in that: The mass percentage of the polyvinyl alcohol aqueous solution is 3%-6%; The doping oxide does not include oxides that are volatile during the sintering process.
4. The method for preparing high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics by controlling defects according to claim 1, characterized in that: The ball milling time is 6-8 hours; the sieving granulation conditions are: selecting uniform powder of 40 mesh to 120 mesh.
5. The method for preparing high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics by controlling defects according to claim 1, characterized in that: The pressing conditions are as follows: 0.15-0.25 g of the mixed powder is pressed into an oxide-doped ZnO green body with a diameter of 8.0 mm and a thickness of 0.75-1.25 mm.
6. The method for preparing high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics by controlling defects according to claim 1, characterized in that: The debinding temperature is 600°C and the debinding time is 2-5 h.
7. The method for preparing high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics by controlling defects according to claim 1, characterized in that: The sintering temperature is 1100° C. and the sintering time is 1-3 h.
8. A high-performance bismuth-free ZnO-Cr2O3-based varistor ceramic, characterized in that: The method for preparing a high-performance bismuth-free ZnO-Cr2O3-based varistor ceramic by controlling defects as described in any one of claims 1 to 7 is adopted, wherein the high-performance bismuth-free ZnO-Cr2O3-based varistor ceramic has Cr enriched in solid solution at the ZnO grain boundaries. 3+ 、Co 3+ and Ca 2+ Oxide; the oxide includes Eu2O3, Dy2O3 or CeO2; and an immovable acceptor defect Ca is formed in the ZnO grain boundary enriched Eu2O3, Dy2O3 or CeO2 × Eu , Ca × Dy or Cr × Ce .
9. The high performance bismuth-free ZnO-Cr2O3-based varistor ceramic according to claim 8, characterized in that: The high-performance bismuth-free ZnO-Cr2O3-based varistor ceramic has a nonlinear coefficient of 66-97, a breakdown field strength of 1441-1830 V / mm, and a leakage current density of 0.12-0.76 μA / cm 2 .
10. Application of high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics prepared by the method for preparing high-performance bismuth-free ZnO-Cr2O3-based varistor ceramics by controlling defects according to any one of claims 1 to 7 in power electronic systems.
Citation Information
Patent Citations
High-nonlinearity rare earth oxide-doped zinc oxide voltage-sensitive ceramic material
CN101823874A
Ultra-high nonlinear ZnO-Bi2O3 based varistor ceramics and preparation method thereof
CN110423110A
A method for obtaining doped zinc oxide varistors, the product obtained by said method and its use
EP2645380A1
Voltage nonnlinear resister
JP1979108297A
Process for producing zno varistor particularly having internal electrode composed of pure silver and sintered at a lower sintering termperature
TW201221501A